Penerapan Senam Bugar Lansia Terhadap Tekanan Darah Pada Lansia Dengan Hipertensi Di Desa Gentan, Bendosari - Septina Wati; Riyani Wulandari (Lembaga Pengembangan Kinerja Dosen, 2023)
Background; The increasing life expectancy of the population causes the number of elderly (elderly) to continue to increase globally, according to the World Health Organization (2019), amounting to 22% of the total world population. Hypertension itself in the elderly, if not treated, causes heart and blood vessel disorders, functional changes, and physical function disorders that will affect Daily Living Activities (ADL). For this reason, there need to be appropriate efforts to overcome hypertension. Elderly fitness gymnastics is a series of forms of physical exercise to increase the strength of the heart muscle. The objectives of the research; were to know the results of the implementation of the application of elderly fitness gymnastics on blood pressure in elderly with hypertension. Methods; This application uses the case study method to determine the decrease in blood pressure values with an Omron digital tensimeter. Result; Blood pressure before doin elderly fitness exercises for respondents in the category of degree 2 hypertension and blood pressure after doing elderly fitness exercises for respondents in the high nornal category. There was decrease blood pressure in respondents after the elderly fitness exercise intervention. Summary; Elderly fitness exercises can reduce the blood pressure of the elderly with hypertension.